Method for preparing silicon-based elastic aerogel phase-change thermal insulation material by in-situ chemical method

By combining in situ chemistry with in situ grafting and supercritical drying, silicon-based elastic aerogel phase change insulation material was prepared, solving the problem of leakage of traditional materials at high temperatures and achieving the safety and efficiency of the materials Thermal insulation.

CN119430198APending Publication Date: 2025-02-14NANJING TECH UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411440629.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Traditional aerogel phase change composite materials are prone to leakage of phase change materials in scenarios higher than the phase change temperature, which affects the safety of the material use.

Method used

In-situ chemistry method is used, and the silicon-based elastic aerogel phase change insulation material is prepared through in-situ grafting method and supercritical drying process to ensure the effective combination of the phase change material and the aerogel and avoid leakage.

Benefits of technology

It realizes the zero leakage characteristics of silicon-based elastic aerogel phase-change thermal insulation material, has low density, high thermal insulation and good mechanical stability, and is suitable for thermal management fields such as lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430198A_ABST
    Figure CN119430198A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation processes of nano-porous materials, and relates to a method for preparing a silicon-based elastic aerogel phase-change thermal insulation material by an in-situ chemical method. A phase-change material with an oxygen-containing functional group on the surface is selected as a phase-change core material, a surfactant, deionized water, ethanol, a silicon precursor, acid, alkali and the phase-change core material are uniformly mixed and subjected to hydrolysis, polycondensation and other reactions, meanwhile, the phase-change core material and silicon-based aerogel are subjected to in-situ grafting combination in the process, and the silicon-based aerogel is prepared. The silicon-based elastic aerogel phase change thermal insulation material is prepared through sol-gel and supercritical drying. The invention innovatively provides an in-situ grafting method, and the constructed silicon-based elastic aerogel phase-change thermal insulation material integrates multiple functions of high thermal insulation property, elasticity, leakage prevention, high response rate and the like, has the advantages of low material cost and convenient preparation process, and is low in energy consumption and easy to realize large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aerogel material preparation technology, and relates to a method for preparing silicon-based elastic aerogel phase change thermal insulation material by an in-situ chemical method such as an in-situ grafting method, a one-step sol-gel method combined with a supercritical drying process, etc. Background Art

[0002] Lithium batteries and other technologies are used as one of the ways of electrochemical energy storage and are widely used in the field of new energy vehicles. However, lithium batteries, which have broad development prospects, have a major safety problem - thermal runaway, which hinders their further market advancement. Therefore, it is particularly important to effectively control the thermal runaway of the battery to prevent the thermal runaway behavior from further deteriorating, thereby increasing the user's escape time. Aerogel, as an insulating material, has extremely low density, extremely low thermal conductivity, and excellent mechanical stability, and is widely used in the field of thermal insulation. Su et al. prepared a laminated silicon carbide-silicon oxide nanowire aerogel, which has mechanical strength and flexibility under compression, tension and bending deformation conditions. The aerogel also has good thermal stability, from -196°C in liquid nitrogen to 1200°C in a butane spray gun, with a thermal conductivity of 0.039.3±0.0004W / (m*K), and has good thermal insulation properties. It can be used as a dynamic thermal sealing material for high-speed aircraft and a thermal insulation material for lunar rovers and deep-sea submersibles (Nature Communications, 2023, 14(1):10.).

[0003] Organic phase change materials have unique physical and chemical properties, with low supercooling, large latent heat of phase change, and non-corrosiveness. They can continuously absorb surrounding heat when the ambient temperature reaches the phase change temperature, and are often used as thermal management materials. Lu et al. prepared hydrothermally treated BN aerogels by a simple hydrothermal method, and encapsulated polyethylene glycol 4000 in the aerogels by vacuum impregnation technology. The highest thermal conductivity of the composite phase change material is 2.62W / (m*K). The BN skeleton serves as a fast channel for phonon transmission, which can effectively reduce thermal resistance. In addition, the aerogel has good mechanical strength, a storage modulus of 169MPa, and significant anti-extrusion ability, which can effectively manage battery thermal management (J Mater Sci Technol, 2023, 160: 248-257). However, the material is obtained by vacuum impregnation. When the temperature is higher than the phase change temperature, a large amount of phase change materials have fluidity, and the thermal conductivity increases. Heat is quickly transferred to other battery components, which will increase the risk of thermal runaway of other battery components.

[0004] Patent CN118222248A uses benzoxazine resin as a raw material to prepare benzoxazine fiber composite aerogel; a subsequent vacuum impregnation method is used to composite phase change material, the impregnation time is relatively long, and there is still a trace amount of leakage after heating at 80°C. Summary of the invention

[0005] The purpose of the present invention is to provide a method and a material preparation process that effectively solves the problem of thermal runaway of batteries, that is, a method for preparing silicon-based elastic aerogel phase change thermal insulation materials by an in-situ chemical method. Traditional aerogel phase change composite materials usually use physical impregnation to achieve the combination of aerogel and phase change materials, but the impregnation method causes the composite material to exhibit the disadvantage of phase change material leakage when encountering a scene higher than the phase change temperature, which not only affects the use of the material, but may even bring risks. The raw materials and preparation methods used in the preparation process developed by this patent are simple, with low energy consumption and controllable structure. The prepared silicon-based elastic aerogel phase change thermal insulation material has the characteristics of anti-leakage, low density, high thermal insulation, etc., which has positive production significance for realizing the application of silicon-based elastic aerogel phase change thermal insulation materials in the fields of thermal protection of lithium batteries.

[0006] The technical solution of the present invention is: a method for preparing a silicon-based elastic aerogel phase change thermal insulation material by an in-situ chemical method, and the specific steps are as follows:

[0007] (1) uniformly mixing a surfactant, an acid, deionized water, and ethanol, and uniformly stirring at 15 to 60° C. and 200 to 1500 r / min with magnetic stirring for 0.5 to 2 h to obtain a transparent solution system;

[0008] (2) adding the silicon precursor to the solution system obtained in step (1), maintaining the same temperature and speed as in step (1) and stirring uniformly for 0.1 to 1 h to obtain a sol system;

[0009] (3) adding the phase change core material having oxygen-containing functional groups on the surface to the sol system obtained in step (2), maintaining the same temperature and speed as step (1) and stirring uniformly for 0.1 to 1.5 hours to obtain a mixed solution;

[0010] (4) adding an alkali catalyst to the solution obtained in step (3), maintaining the same temperature and speed as in step (1) and stirring evenly for 0.1 to 1.5 hours, pouring into a mold and leaving it for 1 to 6 hours to allow it to gel;

[0011] (5) adding the wet gel obtained in step (4) to a replacement solution to replace the obtained wet gel;

[0012] (6) supercritically drying the wet gel obtained in step (5) to obtain a silicon-based elastic aerogel phase change thermal insulation material;

[0013] Wherein: in step (1), the surfactant, acid, deionized water and ethanol are mixed according to the molar ratio of (0.002-0.1):(1-10):(6-30):1; in step (2), the molar ratio of the silicon precursor to ethanol is (0.1-1):1; in step (3), the mass ratio of the phase change core material to ethanol is (0.1-5):1; and in step (4), the molar ratio of the alkali to ethanol is (0.003-0.05):1.

[0014] Preferably, the surfactant described in step (1) is one or more of dodecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, octadecyldimethylbenzylammonium chloride or hexadecylpyridinium chloride.

[0015] Preferably, the acid in step (1) is one of sulfuric acid, hydrochloric acid, nitric acid or acetic acid; the concentration of the acid is 0.02-2 mol / L.

[0016] Preferably, the silicon precursor in step (2) is one or more of dimethyldimethoxysilane, 3-aminopropyltriethoxysilane, methyltrimethoxysilane, tetraethyl orthosilicate or chloropropyltrimethoxysilane.

[0017] Preferably, the phase change core material having oxygen-containing functional groups on the surface described in step (3) is one or more of polyvinyl alcohol, polyethylene glycol, n-decanol, neopentyl glycol, stearic acid, palmitic acid, n-decanoic acid, dodecanoic acid, tetradecanol, octadecyl alcohol, erythritol, mannitol or galactitol.

[0018] Preferably, the base described in step (4) is one of NaOH, KOH, NaHCO3, ammonia or Na2CO3; the concentration of the base is 0.01-2 mol / L.

[0019] Preferably, the aging liquid in step (5) is one or more of methanol, n-pentanol, ethanol, ether or isopropanol. Preferably, the replacement in step (5) is performed 8 to 18 times at room temperature, with an interval of 4 to 12 hours each time.

[0020] Preferably, the drying method in step (6) is a carbon dioxide supercritical drying method: carbon dioxide is used as the drying medium, the reaction temperature is 45-50°C, the pressure in the high-pressure reactor is 8-15MPa, the degassing rate is 2-8L / min, and the drying time is 4-12h.

[0021] This patent introduces phase change materials on the basis of silicon-based aerogel to synergistically improve the thermal insulation performance of aerogel materials and achieve zero leakage of aerogel phase change composite materials. The surface of the phase change material has oxygen-containing functional groups, which can be grafted with the hydroxyl groups on the surface of the aerogel, enhancing the compatibility and bonding between the phase change material and the aerogel. In addition, the phase change core material introduced by the in-situ chemical method is conducive to the improvement of local thermal conductivity, thereby achieving better thermal response, but the entire material is an insulating system, so the material prepared by this patent reaches the appropriate balance point and realizes the efficient application of insulating materials. This patent uses an in-situ grafting method combined with a supercritical drying process to prepare a silicon-based elastic aerogel phase change insulation material. The material exhibits good mechanical elasticity during use, can absorb the impact force of the extrusion process, and has no leakage in a high temperature environment. The preparation of this material will provide an effective solution to problems such as battery thermal management and thermal runaway.

[0022] Beneficial effects:

[0023] The method of the present invention and the silicon-based elastic aerogel phase change thermal insulation material prepared by the method have the following characteristics:

[0024] (1) It is technologically innovative and abandons the traditional impregnation process. The selected phase change material has oxygen-containing functional groups on its surface. The phase change material can be effectively combined with the aerogel by in-situ grafting, thereby improving the mechanical properties, interface bonding strength, local thermal response efficiency and other properties of the overall material.

[0025] (2) The process route is simple. Through a one-step sol-gel method combined with a supercritical drying process, a silicon-based elastic aerogel phase change insulation material can be obtained. The material has excellent shape stability, good elasticity and mechanical stability, and can withstand the extrusion between adjacent battery components during the battery charging and discharging process and bumpy impact.

[0026] (3) The material has the characteristics of high porosity, uniform particles and high thermal insulation, which provides technical support for the application of silicon-based aerogel phase change insulation materials in the field of battery thermal runaway.

[0027] (4) The material did not leak during the high-temperature test, which solved the problem of obvious leakage during use of materials prepared by traditional impregnation process and provided a further protective barrier for the thermal protection of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a physical picture of the silicon-based elastic aerogel thermal insulation phase change material prepared in Example 1;

[0029] Figure 2 is the back temperature rise curve of the silicon-based elastic aerogel thermal insulation phase change material prepared in Example 2 under a 150°C hot plate test;

[0030] Figure 3 This is an infrared thermal image of the silicon-based elastic aerogel thermal insulation phase change material prepared in Example 3 under a 150°C hot plate test; the left side is pure silicon aerogel, and the right side is silicon-based elastic aerogel / polyvinyl alcohol phase change thermal insulation material. DETAILED DESCRIPTION

[0031] Example 1

[0032] Octadecyl dimethyl benzyl ammonium chloride, sulfuric acid, deionized water, and ethanol were mixed evenly in a molar ratio of 0.002:1:20:1, and a transparent solution was obtained after uniform stirring at 15°C and 1300r / min of magnetic stirring for 1.2h, wherein the concentration of the sulfuric acid solution was 2mol / L, and the subsequent steps were carried out at this temperature and speed. Then methyltrimethoxysilane was added to the transparent solution, and a sol solution was obtained after uniform stirring for 1h, wherein the molar ratio of methyltrimethoxysilane to ethanol was 0.3:1. Palmitic acid, a phase change core material, was added to the sol solution, and a mixed solution was obtained after uniform stirring for 1.1h, wherein the mass ratio of palmitic acid to ethanol was 1.7:1. NaOH solution was added to the mixed solution, and after uniform stirring for 1.5h, it was poured into a mold and placed for 3h to wait for its gelation, wherein the molar ratio of NaOH to ethanol was 0.01:1, and the concentration of the NaOH solution was 1mol / L. Ethanol was added to the wet gel for replacement 15 times, with an interval of 6h each time. Then the wet gel after ethanol replacement was dried by supercritical carbon dioxide to obtain a palmitic acid grafted silicon-based elastic aerogel phase change thermal insulation material, wherein the reaction temperature was 45°C, the pressure in the autoclave was 8MPa, the degassing rate was 2L / min, and the drying time was 8h. The actual photo of the obtained silicon-based elastic aerogel phase change thermal insulation material is shown in Figure 1 As shown, it is white, light, has high porosity, and a thermal conductivity of 0.04W / (m*K). It has better thermal insulation performance than pure silicon-based aerogel under a 150°C hot plate test. The back temperature of the aerogel phase change thermal insulation material is stabilized at 40°C after being tested at 150°C for 400s, and there is no leakage during the hot plate test, which has a leakage prevention function.

[0033] Example 2

[0034] Hexadecyltrimethylammonium bromide, hydrochloric acid, deionized water, and ethanol were mixed in a molar ratio of 0.006:2.4:12:1, and stirred evenly for 1.0h at 25°C and 435r / min under magnetic stirring to obtain a transparent solution, wherein the concentration of the hydrochloric acid solution was 0.2mol / L, and the subsequent steps were carried out at this temperature and speed. Then, a mixture of tetraethyl orthosilicate and methyltrimethoxysilane was added to the transparent solution, and stirred evenly for 0.5h to obtain a sol solution, wherein the molar ratio of the mixture of tetraethyl orthosilicate and methyltrimethoxysilane to ethanol was 0.8:1, and the molar ratio of tetraethyl orthosilicate to methyltrimethoxysilane was 1:1. Phase change core material polyethylene glycol was added to the sol solution, and a mixed solution was obtained after uniform stirring for 0.25h, wherein the mass ratio of polyethylene glycol to ethanol was 0.25:1. Add ammonia solution to the mixed solution, stir evenly for 0.1h, pour into a mold and place for 2h to wait for gelation, wherein the molar ratio of ammonia to ethanol is 0.009:1, and the concentration of ammonia solution is 0.5mol / L. Add ethanol to the wet gel for replacement 14 times, with an interval of 12h each time. The wet gel after ethanol replacement is then subjected to supercritical carbon dioxide drying to obtain a polyethylene glycol-grafted silicon-based elastic aerogel phase change insulation material, wherein the reaction temperature is 49°C, the pressure in the high-pressure reactor is 10MPa, the degassing rate is 5L / min, and the drying time is 7h. Figure 2 As shown, the prepared polyethylene glycol grafted silicon-based elastic aerogel phase change thermal insulation material has better thermal insulation performance than pure silicon-based aerogel in a 150°C hot plate test. After being tested at 150°C for 400s, the back temperature is stabilized at 38°C, the thermal conductivity is 0.035W / (m*K), and there is no leakage during the hot plate test, which has an anti-leakage function.

[0035] Example 3

[0036] Dodecyl trimethyl ammonium chloride, nitric acid, deionized water, and ethanol were mixed in a molar ratio of 0.05:5.2:6:1, and stirred evenly at 50 ° C and 680 r / min for 1.6 hours to obtain a transparent solution, wherein the concentration of the nitric acid solution was 0.13 mol / L, and the subsequent steps were carried out at this temperature and speed. Then, a mixture of dimethyldimethoxysilane and 3-aminopropyltriethoxysilane was added to the transparent solution, and stirred evenly for 0.3 hours to obtain a sol solution, wherein the molar ratio of the mixture of dimethyldimethoxysilane and 3-aminopropyltriethoxysilane to ethanol was 0.1:1, and the molar ratio of dimethyldimethoxysilane to 3-aminopropyltriethoxysilane was 1:1. Phase change core material polyvinyl alcohol was added to the sol solution, and a mixed solution was obtained after uniform stirring for 1.5 hours, wherein the mass ratio of polyvinyl alcohol to ethanol was 0.1:1. KOH solution was added to the mixed solution, stirred evenly for 0.4h, poured into a mold and placed for 5h to wait for gelation, wherein the molar ratio of KOH to ethanol was 0.03:1, and the concentration of KOH solution was 0.01mol / L. Methanol was added to the wet gel for replacement 8 times, with an interval of 12h each time. The wet gel after methanol replacement was then subjected to supercritical carbon dioxide drying to obtain a polyvinyl alcohol-grafted silicon-based elastic aerogel phase change insulation material, wherein the reaction temperature was 46°C, the pressure in the high-pressure reactor was 15MPa, the degassing rate was 3L / min, and the drying time was 4h. When the obtained polyvinyl alcohol-grafted silicon-based elastic aerogel phase change insulation material was tested on a hot plate at 150°C, its infrared thermal image showed a lower back temperature than that of pure silicon-based aerogel, and the back temperature was 56.9°C ( Figure 3 ), the thermal conductivity is 0.048W / (m*K), and there is no leakage during the hot plate test, which has anti-leakage function.

[0037] Example 4

[0038] Hexadecyltrimethylammonium chloride, hydrochloric acid, deionized water and ethanol were mixed in a molar ratio of 0.01:7.6:30:1, and a transparent solution was obtained after uniform stirring for 2.0 hours at 60°C and magnetic stirring at 200r / min, wherein the concentration of the hydrochloric acid solution was 1.2mol / L, and the subsequent steps were carried out at this temperature and speed. Then 3-aminopropyltriethoxysilane was added to the transparent solution, and a sol solution was obtained after uniform stirring for 0.1h, wherein the molar ratio of 3-aminopropyltriethoxysilane to ethanol was 0.6:1. Phase change core material stearic acid was added to the sol solution, and a mixed solution was obtained after uniform stirring for 0.1h, wherein the mass ratio of stearic acid to ethanol was 3:1. Na2CO3 solution was added to the mixed solution, and after uniform stirring for 0.8h, it was poured into a mold and placed for 4h to wait for its gelation, wherein the molar ratio of Na2CO3 to ethanol was 0.003:1, and the concentration of Na2CO3 solution was 2mol / L. Isopropanol was added to the wet gel for replacement 8 times, with an interval of 12 hours each time. The wet gel after isopropanol replacement was then subjected to carbon dioxide supercritical drying to obtain a stearic acid-grafted silicon-based elastic aerogel phase change thermal insulation material, wherein the reaction temperature was 47°C, the pressure in the high-pressure reactor was 11.5MPa, the degassing rate was 6L / min, and the drying time was 12h. The obtained stearic acid-grafted silicon-based elastic aerogel phase change thermal insulation material was tested at 200°C for 400s, and the back temperature was stabilized at 65.7°C, the thermal conductivity was 0.046W / (m*K), and there was no leakage during the hot plate test, which had a leak-proof function.

[0039] Example 5

[0040] Hexadecylpyridinium chloride, acetic acid, deionized water and ethanol were mixed in a molar ratio of 0.1:10:26:1, and a transparent solution was obtained after uniform stirring at 45°C and 1050r / min of magnetic stirring for 0.5h, wherein the concentration of the acetic acid solution was 0.02mol / L, and the subsequent steps were carried out at this temperature and speed. Then chloropropyltrimethoxysilane was added to the transparent solution, and a sol solution was obtained after uniform stirring for 0.8h, wherein the molar ratio of chloropropyltrimethoxysilane to ethanol was 1:1. Octadecanol, a phase change core material, was added to the sol solution, and a mixed solution was obtained after uniform stirring for 0.75h, wherein the mass ratio of octadecyl alcohol to ethanol was 5:1. NaHCO3 solution was added to the mixed solution, and after uniform stirring for 1.3h, it was poured into a mold and placed for 6h to wait for its gelation, wherein the molar ratio of NaHCO3 to ethanol was 0.05:1, and the concentration of NaHCO3 solution was 0.12mol / L. The wet gel was replaced by n-pentanol 18 times, with an interval of 8 hours each time. The wet gel replaced by n-pentanol was then supercritically dried with carbon dioxide to obtain a silicon-based elastic aerogel phase change thermal insulation material grafted with octadecyl alcohol, wherein the reaction temperature was 45°C, the pressure in the autoclave was 13MPa, the degassing rate was 8L / min, and the drying time was 7.5h. The obtained silicon-based elastic aerogel phase change thermal insulation material grafted with octadecyl alcohol was tested at 300°C for 400s, and the back temperature was stable at 72.4°C, the thermal conductivity was 0.044W / (m*K), and there was no leakage during the hot plate test, which had a leakage prevention function.

Claims

1. A method for preparing a silicon-based elastic aerogel phase change thermal insulation material by an in-situ chemical method, the specific steps of which are as follows: (1) uniformly mixing a surfactant, an acid, deionized water, and ethanol, and uniformly stirring at 15 to 60° C. and 200 to 1500 r / min with magnetic stirring for 0.5 to 2 h to obtain a transparent solution system; (2) adding a silicon precursor to the solution system obtained in step (1), maintaining the same temperature and speed as in step (1) and stirring uniformly for 0.1 to 1 h to obtain a sol system; (3) adding the phase change core material having oxygen-containing functional groups on the surface to the sol system obtained in step (2), maintaining the same temperature and speed as step (1) and stirring uniformly for 0.1 to 1.5 hours to obtain a mixed solution; (4) adding an alkali catalyst to the solution obtained in step (3), maintaining the same temperature and speed as in step (1) and stirring evenly for 0.1 to 1.5 hours, pouring into a mold and leaving it for 1 to 6 hours to allow it to gel; (5) adding the wet gel obtained in step (4) to a replacement solution to replace the obtained wet gel; (6) supercritically drying the wet gel obtained in step (5) to obtain a silicon-based elastic aerogel phase change thermal insulation material; in: In step (1), the surfactant, acid, deionized water and ethanol are mixed in a molar ratio of (0.002-0.1):(1-10):(6-30):1; in step (2), the molar ratio of the silicon precursor to ethanol is (0.1-1):1; in step (3), the mass ratio of the phase change core material to ethanol is (0.1-5):1; and in step (4), the molar ratio of the alkali to ethanol is (0.003-0.05):

1.

2. The method according to claim 1, characterized in that The surfactant described in step (1) is one or more of dodecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, octadecyldimethylbenzylammonium chloride or hexadecylpyridinium chloride.

3. The method according to claim 1, characterized in that The acid described in step (1) is one of sulfuric acid, hydrochloric acid, nitric acid or acetic acid; the concentration of the acid is 0.02-2 mol / L.

4. The method according to claim 1, characterized in that The silicon precursor described in step (2) is one or more of dimethyldimethoxysilane, 3-aminopropyltriethoxysilane, methyltrimethoxysilane, tetraethyl orthosilicate or chloropropyltrimethoxysilane.

5. The method according to claim 1, characterized in that The phase change core material having oxygen-containing functional groups on the surface described in step (3) is one or more of polyvinyl alcohol, polyethylene glycol, n-decanol, neopentyl glycol, stearic acid, palmitic acid, n-decanoic acid, dodecanoic acid, tetradecanol, octadecyl alcohol, erythritol, mannitol or galactitol.

6. The method according to claim 1, characterized in that The base described in step (4) is one of NaOH, KOH, NaHCO3, ammonia or Na2CO3; the concentration of the base is 0.01-2 mol / L.

7. The method according to claim 1, characterized in that The aging liquid in step (5) is one or more of methanol, n-pentanol, ethanol, ether or isopropanol.

8. The method according to claim 1, characterized in that The drying method in step (6) is a carbon dioxide supercritical drying method: carbon dioxide is used as the drying medium, the reaction temperature is 45-50°C, the pressure in the high-pressure reactor is 8-15MPa, the degassing rate is 2-8L / min, and the drying time is 4-12h.

Citation Information

Cited By

  • Flame-retardant bio-based benzoxazine aerogel composite phase change material and preparation method thereof

    CN120399645A

  • Silicon dioxide aerogel composite phase change thermal management material and preparation method thereof

    CN121895923A